Box-Behnken Design Approach to Develop and Optimize Mannose-Conjugated Genistein-Loaded Transferosomal Gel - Sarwa, Dr. Khomendra Kumar (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: The present study aims to develop and optimize the mannose-conjugated genistein-loaded transferosomal gel of by Box-Behnken design to maximize entrapment efficiency, and drug loading with the lowest vesicle size. Methods: Mannose-conjugated genistein-loaded transferosomes were prepared by the thin film hydration method and optimised the formulation using the Box-Behnken a full factorial central composite design. The formulations were characterized for particle size, zeta potential, poly dispersibility index, entrapment efficiency and drug content. Contour plots and surface plots were used to predict the final composition of the optimized formulation of the genistein-loaded transferosome. In this optimized formulation mannose was conjugated and prepared mannose-conjugated genisteinloaded transferosomes. This vesicle system was incorporated into Carbopol 940 gel for topical delivery. The final gel formulation was characterized for homogeneity, pH, spreadability, dynamic viscosity and drug content. Results: The formulation has shown a particle size of 182.0 nm, PDI0.268, zeta potential -28.4 entrapment efficiency of 78.25%±0.06, and drug loading of 68.26% ± 1.23. Spherical shape particles found in the Transmission Electron Microscopic image have the mean particle size scale and were found to be in the nano-formulation range (less than 200 nm). Mannoseconjugated genistein-loaded transferosomal gel was found suitable for topical delivery with favourable pH, viscosity, spreadability and drug content. Conclusion: The study revealed that both genistein-loaded transferosomes and mannoseconjugated genistein-loaded transferosomes formulations were successfully optimized by Box-Behnken Design. Both the gel preparations confirming the physical characteristics parameters were found in an acceptable range.